COMPLICATED TUBERCULOSIS IN A 13 YEAR OLD CHILD WITH DOWN SYNDROME - A CASE REPORT - Nestorov, Hristijan; Boshkovska, Katerina; Doksimovski, Filip; Chakalarovska, Irena; Ivanovska, Julija; Aleksovski, Zlatko (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Tuberculosis (TB) is the most common cause of infectious disease-related mortality worldwide. Most persons infected wonâ€™t develop active disease, but in certain instances such as extremes of age or defects in cell-mediated immune response, TB may develop. Down syndrome (DS) is the most common neurodevelopmental disorder of know genetic cause and described simply as arising from an extra copy of chromosome 21, presenting with characteristic features. Due to immune defects, DS suffer more frequently from respiratory tract infections than normal children. We present a case of a 13 years old child with Down Syndrome who was diagnosed with lung tuberculosis, after a right sided lobectomy due to a lung abscess. The child was hospitalized, following a period of one and a half month with fever and vomiting that did not improve with therapy. Investigations were made, including CT scan on the lungs. Due to right sided empyema and abscess on the right upper lobe, right sided lobectomy was preformed. The postsurgical pathohistological findings were in addition to pulmonary tuberculosis. Four drug anti tuberculosis regimen was started.  The four-drug course was given for two months, and then a two-drug regime was continued. To this day the child is on the sixth month of the two-drug anti tuberculosis regime. CT scans, regular Chest X-rays and ultrasound of the lungs were made, with gradual improvement. In Down syndrome patients who have a complicated pneumonia that doesnâ€™t respond to standard treatment, a tuberculosis disease should be considered. Key words: child, down syndrome, tuberculosis.